Peran Mediasi Motivasi Kerja dalam Pengaruh Perceived Organizational Support dan Employee Engagement terhadap Organizational Citizenship Behaviour : (Studi pada Pegawai Pusat Jasa Kearsipan, Arsip Nasional Republik Indonesia) - Syiffa Chaerunisa; Zulvia Khalid (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to examine The Role of Work Motivation Mediation in the Influence of Perceived Organizational Support and Employee Engagement on Organizational Citizenship Behaviour in employees of the Pusat Jasa Kearsipan, Arsip Nasional Republik Indonesia. The employee population at the Pusat Jasa Kearsipan, Arsip Nasional Republik Indonesia is 55 people. The sample used in this study is using a saturated sample. Data was collected through a questionnaire with a likert scale processed using Microsoft Excel 2013 software and Smart PLS 4.1 version. The research method used is SEM PLS. The results of this study show that the variable perceived organizational support has a not significant effect on organizational citizenship behavior, employee engagement has a not significant effect on organizational citizenship behavior and work motivation has a significant effect on organizational citizenship behavior. The results of the study also showed that there was a significant influence of perceived organizational support on work motivation, and a significant effect of employee engagement on work motivation. This study also results that work motivation is stated to be able to mediate perceived organizational support for organizational citizenship behaviour, and work motivation is also able to mediate employee engagement towards organizational citizenship behaviour at the Pusat Jasa Kearsipan, Arsip Nasional Republik Indonesia.